2007
DOI: 10.1103/physrevlett.99.117601
|View full text |Cite
|
Sign up to set email alerts
|

High-Pressure Study of X-Ray Diffuse Scattering in Ferroelectric Perovskites

Abstract: We present a high-pressure x-ray diffuse scattering study of the ABO3 ferroelectric perovskites BaTiO3 and KNbO3. The well-known diffuse lines are observed in all the phases studied. In KNbO3, we show that the lines are present up to 21.8 GPa, with constant width and a slightly decreasing intensity. At variance, the intensity of the diffuse lines observed in the cubic phase of BaTiO3 linearly decreases to zero at ∼ 11 GPa. These results are discussed with respect to x-ray absorption measurements, which leads t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(43 citation statements)
references
References 37 publications
3
39
0
1
Order By: Relevance
“…The microscopic nature of these polar precursors has recently been revealed by x-ray absorption fine structure 10 and nuclear magnetic resonance measurements 11 to be composed of dynamic off-center displacements of Ti ions along eight equivalent ͗111͘ directions, consistent with the original eight-site model suggested for the order-disorder component in BaTiO 3 . 4 However, although the disorder at the B-site ions is expected to enhance the ferroelectric instability, 12 exact roles and microscopic natures of displacive and order-disorder components during the phase transition are still controversial. In addition, the relation of two-mode behaviors, recently revealed by a first-principles-based calculation and far-infrared reflectivity measurements, 13 to these two phase-transition components remains far from complete understanding.…”
Section: 2mentioning
confidence: 99%
“…The microscopic nature of these polar precursors has recently been revealed by x-ray absorption fine structure 10 and nuclear magnetic resonance measurements 11 to be composed of dynamic off-center displacements of Ti ions along eight equivalent ͗111͘ directions, consistent with the original eight-site model suggested for the order-disorder component in BaTiO 3 . 4 However, although the disorder at the B-site ions is expected to enhance the ferroelectric instability, 12 exact roles and microscopic natures of displacive and order-disorder components during the phase transition are still controversial. In addition, the relation of two-mode behaviors, recently revealed by a first-principles-based calculation and far-infrared reflectivity measurements, 13 to these two phase-transition components remains far from complete understanding.…”
Section: 2mentioning
confidence: 99%
“…D'abord parce que les progrès en matière de techniques expérimentales permettent occasionnellement de « revisiter » des problèmes non résolus [61][62][63][64][65]. Et ensuite parce que les « nouveaux » matériaux s'avèrent aussi riches en instabilités structurales de toutes sortes, que les autres et il est toujours souhaitable, même si cela ne constitue pas un objet de recherche en soi, de savoir identifier les mécanismes qui donnent lieu à ces changements de structure, ne serait-ce que pour mieux comprendre en quoi ils peuvent affecter les propriétés « utiles » des dits matériaux.…”
Section: Resultsunclassified
“…Using single-crystal diffuse scattering measurements with laboratory X-rays, the 1-dimensional correlations among B-atom displacements in BaTiO 3 and KNbO 3 were earlier estimated to be between 50 Å and 100 Å [54,55]. More recent measurements with high-energy X-rays provide estimates of the order of 2 nm [56,57], which is closer to that predicted from theoretical calculations [58]. In addition to 1-dimensional correlations, 2-dimensional correlations in the form of nanoscale polar clusters among B-atom off-center displacements are also possible [59,60].…”
Section: Atomic Displacement Disordermentioning
confidence: 99%
“…Most remarkably, in situ diffraction with synchrotron X-rays have shown that the nanoscale correlations for atomic displacements in both BaTiO 3 and KNbO 3 are highly susceptible to applied pressure and electric fields. The susceptibility of B-site atomic displacements on applied pressure was studied by Ravy et al from in situ high-energy X-ray diffraction experiments [56]. They showed that the intensity of the diffuse scattering lines, as described above, are strong functions of the magnitude of applied pressures.…”
Section: Atomic Displacement Disordermentioning
confidence: 99%